Norepinephrine represses the expression of toxA and the siderophore genes in Pseudomonas aeruginosa - Li, Wang (2009)
Among the different extracellular virulence factors produced by Pseudomonas aeruginosa are exotoxin A (ETA) and the pyoverdine and pyochelin siderophores. Production of ETA and the siderophores requires the function of the iron-starvation sigma factor PvdS, the transcriptional activator RegA, and the AraC-activator PchR. Iron represses production of ETA and the siderophores by repressing expression of pvdS, regA, and pchR. PvdS regulates the expression of the ETA gene, toxA, regA, and the pyoverdine synthesis genes. The catecholamine norepinephrine (NE) enhances the growth of pathogenic bacteria by transferring iron from host binding proteins. In this study, we elucidated the mechanism by which NE and other catecholamines induce P. aeruginosa growth. We also investigated if NE regulates expression of toxA and the siderophore genes; and the mechanism of this regulation. NE enhanced the growth of P. aeruginosa by supplying iron from transferrin. This provision of iron repressed expression of toxA, the pyoverdine genes pvdD and pvdE, and their regulators, pvdS, regA, and pchR, suggesting that NE accomplishes this repression through PvdS and PchR. Additionally, NE bypassed PvdS and supported the growth of a pvdS deletion mutant indicating that NE transfers iron to P. aeruginosa independently of pyoverdine. Thus, NE apparently influences the pathogenesis of P. aeruginosa by affecting its pattern of growth and the production of virulence factors.